2015
DOI: 10.3389/fmicb.2015.00605
|View full text |Cite
|
Sign up to set email alerts
|

Proteome profiling of heat, oxidative, and salt stress responses in Thermococcus kodakarensis KOD1

Abstract: The thermophilic species, Thermococcus kodakarensis KOD1, a model microorganism for studying hyperthermophiles, has adapted to optimal growth under conditions of high temperature and salinity. However, the environmental conditions for the strain are not always stable, and this strain might face different stresses. In the present study, we compared the proteome response of T. kodakarensis to heat, oxidative, and salt stresses using two-dimensional electrophoresis, and protein spots were identified through MALDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…The thermosome is a class II chaperonin that represents large, barrel-shaped double-ring ATPases. Thermosomes are under study in hyperthermophiles where they are considered crucial for survival (Jia et al, 2015). Our observation may suggest that such class II chaperonins have a broader functional role than previously thought.…”
Section: Resultsmentioning
confidence: 99%
“…The thermosome is a class II chaperonin that represents large, barrel-shaped double-ring ATPases. Thermosomes are under study in hyperthermophiles where they are considered crucial for survival (Jia et al, 2015). Our observation may suggest that such class II chaperonins have a broader functional role than previously thought.…”
Section: Resultsmentioning
confidence: 99%
“…gammatolerans 虽然在基因组中并未预测到Pro和Ile的合成途径, 但 却不需要在培养基中添加这两种氨基酸作为必需氨 基酸 [29] . 种胁迫响应共有的上调表达途径 [46] . 此外, 对Thermo-…”
Section: 生理特性unclassified
“…The fungal secondary metabolites benzenediol lactone polyketides, which are important pharmacophores, participate in the heat shock response (Xu et al ., ). In the model microorganism Thermococcus kodakarensis KOD1, heat stress induces the upregulation of proteins, identified through MALDI‐TOF/MS, related to secondary metabolite synthesis by KEGG pathway analysis (Jia et al ., ). Our recent research also showed a significant increase in GA content after HS in G. lucidum (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%